Gene cloning and molecular characterization of a thermostable chitosanase from Bacillus cereus TY24 - Rong-Xian Zhang; Zhong-Wei Wu; Shu-Juan Zhang; Hui-Min Wei; Cheng-Wei Hua; Lan Li; Tian-You Yang (BMC Biotechnology, 2022)
Abstract Background An important conceptual advance in health and the environment has been recognized that enzymes play a key role in the green processing industries. Of particular interest, chitosanase is beneficial for recycling the chitosan resource and producing chitosan oligosaccharides. Also, chitosan gene expression and molecular characterization will promote understanding of the biological function of bacterial chitosanase as well as explore chitosanase for utilizing chitosan resources. Results A chitosanase-producing bacterium TY24 was isolated and identified as Bacillus cereus. Moreover, the chitosanase gene was cloned and expressed in Escherichia coli. Sequence analysis reveals that the recombinant chitosanase (CHOE) belongs to the glycoside hydrolases 8 family. The purified CHOE has a molecular weight of about 48 kDa and the specific activity of 1150 U/mg. The optimal pH and temperature of CHOE were 5.5 and 65 °C, respectively. The enzyme was observed stable at the pH range of 4.5–7.5 and the temperature range of 30–65 °C. Especially, the half-life of CHOE at 65 °C was 161 min. Additionally, the activity of CHOE was remarkably enhanced in the presence of Mn2+, Cu2+, Mg2+ and K+, beside Ca2+ at 5 mM. Especially, the activity of CHOE was enhanced to more than 120% in the presence of 1% of various surfactants. CHOE exhibited the highest substrate specificity toward colloid chitosan. Conclusion A bacterial chitosanase was cloned from B. cereus and successfully expressed in E. coli (BL21) DE3. The recombinant enzyme displayed good stability under acid pH and high-temperature conditions.